2017
DOI: 10.14336/ad.2016.1228
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Readmission Risk and Mortality after Hip Fracture Surgery: A National Population-Based Study in Taiwan

Abstract: Early readmission following hip fracture (HFx) is associated with high morbidity and mortality. We conducted a survival analysis of patients with readmission within 1 year after HFx to elucidate the trend and predictors for readmission. We used Taiwan National Health Insurance Database to recruit HFx patients who underwent operations between 2000 and 2009. Patients < 60 years; with pathological fractures; involved in major traffic accidents; with previous pelvis, femur, and hip operations; or who died during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 36 publications
1
26
2
Order By: Relevance
“…They have been associated with increased morbidity, loss of autonomy in Activities of Daily Living (ADLs), high rate of institutionalization and mortality 4,5 . The mortality in the first year after hip fractures surgery is high, ranging between 15% and 36% 4,69 . Dubljanin-Raspopovic et al .…”
Section: Introductionmentioning
confidence: 99%
“…They have been associated with increased morbidity, loss of autonomy in Activities of Daily Living (ADLs), high rate of institutionalization and mortality 4,5 . The mortality in the first year after hip fractures surgery is high, ranging between 15% and 36% 4,69 . Dubljanin-Raspopovic et al .…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by Lee et al (31) and concerned with one-year readmission risk and mortality after hip fracture surgery concluded that, In this population-based study of 5442 patients who underwent surgical treatment of hip fractures, we found the predictive factors for readmission included male gender, older age, a higher number of comorbidities, and a longer hospital stay in both early and late readmission groups. A higher risk of readmission is observed during the first 30 days of follow-up.…”
Section: Introductionmentioning
confidence: 47%
“…In 2011, 10.7% of the entire population was ≥ 65 years old; this figure is more than 14% in 2017. [ 4 ] Some authors concluded that a relationship between vertebral deformities and hip fracture that vertebral deformities have in prospective studies been reported as a risk factor for a future hip fracture. [ 5 8 ]…”
Section: Introductionmentioning
confidence: 99%